Optimization of Bone Health in Children before and after Renal Transplantation: Current Perspectives and Future Directions - Sgambat, Kristen; Moudgil, Asha (Frontiers in Pediatrics, 2014)
The accrual of healthy bone during the critical period of childhood and adolescence sets the stage for lifelong skeletal health. However, in children with chronic kidney disease (CKD), disturbances in mineral metabolism and endocrine homeostasis begin early on, leading to alterations in bone turnover, mineralization, and volume, and impairing growth. Risk factors for CKD-mineral and bone disorder (CKD-MBD) include nutritional vitamin D deficiency, secondary hyperparathyroidism, increased fibroblast growth factor 23 (FGF23), altered growth hormone and insulin like growth factor-1 (GH/IGF-1) axis, delayed puberty, malnutrition, and metabolic acidosis. After kidney transplantation, nutritional vitamin D deficiency, persistent hyperparathyroidism, tertiary FGF23 excess, hypophosphatemia, hypomagnesaemia, immunosuppressive therapy, and alteration of sex hormones continue to impair bone health and growth. As function of the renal allograft declines over time, CKD-MBD associated changes are reactivated, further impairing bone health. Strategies to optimize bone health post-transplant include healthy diet, weight-bearing exercise, correction of vitamin D deficiency and acidosis, electrolyte abnormalities, steroid avoidance, and consideration of recombinant human growth hormone therapy. Other drug therapies have been used in adult transplant recipients, but there is insufficient evidence for use in the pediatric population at the present time. Future therapies to be explored include anti-FGF23 antibodies, FGF23 receptor blockers, and treatments targeting the colonic microbiota by reduction of generation of bacterial toxins and adsorption of toxic end products that affect bone mineralization.